Pomen knjižnice kot javnega prostora - knjižnica kot "tretji prostor" - Podgornik, Valentina (Knjižnica, 2019)
The article is a reflection on the importance of a library as a public space as well as a "third place". Public libraries are far from being just the institutions that collect, catalogue, store and make available library materials. They are social spaces able to connect people of different believes, cultures and interests. They are a part of public cultural and educational infrastructures at a local level that are available to everybody on equal terms. The importance of library spaces for their users is multi-layered and it depends mostly on their needs and the needs of the local community. Public libraries are institutions of lifelong learning that not only offer basic services but also provide the feeling of homeliness, warmth, well-being, safety and shelter. However, they must be a regular feature in the life of people who are using them. "Third places" are informal spaces, which enable people to meet socialize and connect and to make new friendships. Thus, they provide the space for social interactions, and building social capital. A literature review presents and explains the concept of a "third place" that has been emerging for a long time in connection with the development of public libraries, but is difficult to understand - to what purpose it serves or what it actually is. This article determines to what extent the activities of the France Bevk Public Library Nova Gorica meets the definition of the "third place". It is mostly based upon subjective observation and reflection on the subject, on personal experience and perception. It is also supported by the exchange of opinions with members and visitors attending the events at the France Bevk Public Library and the users of its services.
Keywords: družbena vloga; Goriška knjižnica Franceta Bevka; javni prostori; Nova Gorica; socialni kapital; sodobne tehnologije; splošne knjižnice